Two new species of Halictophagidae (Insecta: Strepsiptera) including the first record of genus Coriophagus Kinzelbach from India - Roy, Sukhendu; Hazra, Niladri (Zootaxa, 2016)
Coriophagus calcaneus n. sp. (Coriophaginae) and Halictophagus prominens n. sp. (Halictophaginae) are described from India. Coriophagus calcaneus is the first record of the genus Coriophagus Kinzelbach from India. The genus Coriophagus is restricted in the Gondwanaland, while Halictophagus Curtis has a cosmopolitan distribution.